The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1177/20539517211063689
|View full text |Cite
|
Sign up to set email alerts
|

‘The interface of the future’: Mixed reality, intimate data and imagined temporalities

Abstract: This article examines discourses about mixed reality as a data-rich sensing technology – specifically, engaging with discourses of time as framed by developers, engineers and in corporate PR and marketing in a range of public facing materials. We focus on four main settings in which mixed reality is imagined to be used, and in which time was a dominant discursive theme – (1) the development of mixed reality by big tech companies, (2) the use of mixed reality for defence, (3) mixed reality as a technology for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While Meta dominates much of the spatial computing market, other firms compete in the space. As previous research by Egliston and Carter (2022b) has revealed, the way that competitors (such as Microsoft or Vuzix) have sought to grow the influence of their spatial computing (largely AR) offerings has been through contracts with various arms of the state – such as the military and police. Comparative study across the wider sector may provide entry points for further work by scholars, policymakers and regulators.…”
Section: Discussionmentioning
confidence: 99%
“…While Meta dominates much of the spatial computing market, other firms compete in the space. As previous research by Egliston and Carter (2022b) has revealed, the way that competitors (such as Microsoft or Vuzix) have sought to grow the influence of their spatial computing (largely AR) offerings has been through contracts with various arms of the state – such as the military and police. Comparative study across the wider sector may provide entry points for further work by scholars, policymakers and regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the Pluriverse project situates itself as the dialectical opposite of the version of the Web3 Metaverse being built by platforms like Meta/Facebook where data extraction and monetization is a driving force (Egliston and Carter, 2022) and by startups like Decentraland that are playing out colonial fantasies by creating, enclosing, and selling “virtual real estate” tied to NFTs (Ravenscraft, 2021). Instead, Verses aims to advance an alternative for Web3 “stands in contrast to existing applications of blockchain technology, which often emphasize speculation, and create artificial scarcities of capital and attention” (Verses, 2022).…”
Section: Decentralization: Background On a Conceptual Battlementioning
confidence: 99%
“…Mixed reality (MR) is an advanced form of the AR paradigm in which synthetic data is not only layered: instead, virtual objects are completely integrated within the real environment and can interact with it. The physical real world and the virtual computer-generated objects are difficult to distinguish [ 3 ].…”
Section: Background and Significancementioning
confidence: 99%